Establishment of the reproducible branch retinal artery occlusion mouse model and intravital longitudinal imaging of the retinal CX3CR1-GFP+ cells after spontaneous arterial recanalization - Jeon, Jehwi; Kim, Sang-Hoon; Kong, Eunji; Kim, Soo Jin; Yang, Jee Myung; Lee, Joo Yong; Lee, Junyeop; Kim, You-Me; Kim, Pilhan (Frontiers in Medicine, 2022)
Animal models of retinal artery occlusion (RAO) have been widely used in many studies. However, most of these studies prefer using a central retinal artery occlusion (CRAO) that is a typical global ischemia model of the retina, due to the technical limitation of producing single vessel targeted modelling with real-time imaging. A focal ischemia model, such as branch retinal artery occlusion (BRAO), is also needed for explaining interactions, including the immunological reaction between the ischemic retina and adjacent healthy retina. Accordingly, a relevant model for clinical RAO patients has been demanded to understand a pathophysiology of the RAO disease. Herein, we establish a convenient BRAO mouse model to research focal reaction of the retina. As a photo-thrombotic agent, Rose bengal was intravenously injected into 7 week-old transgenic mice (CX3CR1-GFP, for microglial visualization) for making embolism occlusion, which causes pathology similarly to clinical cases. In an optimized condition, a 561nm laser (13.1 mw) was projected to a targeted vessel to induce photo-thrombosis for 27 seconds by custom-built retinal confocal microscopy. Compared to previous BRAO models, the procedures of thrombosis generation were naturally and minimal invasively generated with real-time retinal imaging. In addition, by utilizing the self-remission characteristics of Rose bengal thrombus, a reflow of the BRAO with immunological reactions of the retinal microglia was monitored and analyzed. In this models, reperfusion began at day 3 after modelling. Simultaneously, the activation of the retinal microglia, including the increase of activation marker and morphologic change, was confirmed by immunohistochemical (IHC) staining and quantitative real-time PCR. CD86 and Nox2 were prominently expressed at day 3 after the modelling. At day 7, blood flow was almost restored in the large vessels. Microglial populations in both the inner plexiform layer and outer plexiform layer also increased around even in the BRAO peri-ischemic area. In summary, this study successfully establishes a reproducible BRAO modelling method with convenient capabilities of easily controllable time points and selection of a specific single vessel. It can be a useful tool to analyze the role of retinal microglia in ischemic-reperfusion (IR) injury after BRAO and further investigate the pathophysiology of BRAO.